Teachers’ and Students’ Reflection on the Problem of Writing Narrative Text in a Remote Area (Flores Island) - Darmawan Labira (LET: Linguistics, Literature and English Teaching Journal)
This study investigated teachers' and students' reflection on the problem of writing narrative text in a remote area. The data were taken from 30 students and 15 EFL teachers from purposely selected schools that have reputations of being the best and largest school in the Sikka regency using written test to find out the students’ abilities in writing narrative text. The researcher used questionnaire to collect the data regarding student experiences and experiences. The finding indicated grammatical aspect as the biggest student’s problem (25 errors), the mechanic aspect of writing revealed 24 errors, 23 errors in vocabulary aspect, writing content revealed 20 errors, writing organization revealed 20 errors. The problems raised when students started to put words on paper, students forgot their storytelling abilities: students couldn’t think of topics; omitted relevant details, but go on and on about irrelevant ones; their dialogue was bland; couldn’t figure out how to start and how to end. Grammar and vocabulary were mostly performed in writing activities, most teachers used 50-minute time allocations for writing practices and pictures to pictures model was mostly adopted by teachers.